Potensi Bakteri Endofit dari Batang Panili Sehat sebagai Agen Pengendali Hayati Fusarium oxusporum f. sp. vanillae Penyebab Busuk Batang Panili - SUNITI, NI WAYAN (Agrotrop : Journal on Agriculture Science; Vol 5 No 1 (2015))
The potential of Endophytic Bacteria from Shoot of healthy Vanilla for Biological Control Agenst of Fuxarium oxusporum f. sp. vanilla. The aim of the research was to determine in-vitro inhibitory of endophytic bacteria from healthy stem of vanilla against stem rot dideases caused by Fusarium oxysporum f.sp. vanillae The research was conducted in Phythopatology Laboratory and green house Fakulty of Agiculure from January to August 2014. The results showed that 50 isolates of endophytic bacteria can be isolated from Tabanan and Badung regency. Antagonistic test results from 50 isolate of endophytic bacteria found the six isolates of endophytic bacteria has potential as antagonists against Fusarium oxysporum f.sp. vanillae namely Endophytic Tabanan 1 (T1), T7, T13, Endophytic Badung 28(B28), B30 and B41. In-vitro test showed endophytic bacteria isolate T1 has the highestinhibition to the F. oxysporum f.sp. vanillae growth by 87%. Results of the research in Greenhouse, endophytic bacteria isolate T1 can stimulate the growth of shoots and capable of protecting plants from vanilla stem rot diseases with the lowest attack percentage of 32%.
Keywords: Endophytic bacteria, inhibition, Fusarium oxysporum, vanilla (Vanilla planifolia)